2007
DOI: 10.1063/1.2800822
|View full text |Cite
|
Sign up to set email alerts
|

High-oxygen-pressure crystal growth of ferroelectric Bi4Ti3O12 single crystals

Abstract: We have investigated the effects of high-oxygen-pressure crystal growth of ferroelectric Bi4Ti3O12 on the polarization properties along the a(b) axis. Domain observations by piezoresponse force microscope demonstrate that a small remanent polarization (Pr) for the crystals grown at 0.02MPa is attributed to the clamping of 90° domain walls by oxygen vacancies. The vacancy formation of Bi and O during crystal growth at high temperatures is suppressed at a higher oxygen pressure, leading to a larger Pr of 47μC∕cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 22 publications
1
41
0
Order By: Relevance
“…180° domains can be easily switched by E application compared with 90° domains and the volume of the backswitched 180° domains is small. 95) In contrast, 90° domains play a dominant role in the values of Pr and d33, as a result of the reorientation of 90° domain configurations in BNT-BT crystals (see Fig. 7).…”
Section: Reorientation Of Domain Structure Leading To Poor Propertiesmentioning
confidence: 99%
“…180° domains can be easily switched by E application compared with 90° domains and the volume of the backswitched 180° domains is small. 95) In contrast, 90° domains play a dominant role in the values of Pr and d33, as a result of the reorientation of 90° domain configurations in BNT-BT crystals (see Fig. 7).…”
Section: Reorientation Of Domain Structure Leading To Poor Propertiesmentioning
confidence: 99%
“…8,9 Besides Bi 4 Ti 3 O 12 and its derivatives with three layers of TiO 6 octahedra, SrBi 2 Ta 2 O 9 is another kind of bismuth layer-structured ferroelectric material with m = 2 that shows excellent ferroelectric properties, which have been well studied. 8,10 In comparison to the volume of work that has been done on the above two systems with m = 2 and 3, there is still a great deal of work that should be done on those Aurivillius phase bismuth layerstructured ferroelectrics with m = 4. For example, although some ferroelectrics in this family of materials, such as ABi 4 Ti 4 O 15 ͑A = Ca, Ba, Sr, and Pb͒, have been studied in the form of thin films, bulk ceramics, and single crystals, one of its derivatives, M 0.5 Bi 4.5 Ti 4 O 15 ͑M = Na and K͒ has only been studied in ceramic and single crystal forms.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned before, the piezoelectric response and polarization are not a strong function of temperature at the temperatures well below Curie temperature. Previous paper reported that the created oxygen vacancy defect dipoles could pin the domain walls, 9) so that this result might be caused by the volatilization of Bi 2 O 3 during the calcination or the sintering. However, in this study, it was unclear that oxygen vacancy was originated from the volatilization of Bi 2 O 3 or valence changing of iron during the sintering.…”
Section: Resultsmentioning
confidence: 99%